East Indian Minstrels - (:unkn) unknown (Muir, Marshall and Co., Trinidad, 2008)
Three East Indian musical performers with traditional Indian instruments.
Colour: Black and White; Style: Portrait; Other: Bordered, Undivided
Keywords: Postcards; Minstrels--Trinidad and Tobago; Musicians--Trinidad and Tobago; East Indians--Trinidad and Tobago; Trinidad and Tobago; Musical instruments--India; Men--Trinidad and Tobago